Information disclosure through technology licensing - Arijit Mukherjee; Aniruddha Bagchi (Games, 2020)
We show that even if information transmission through an honest outside agency is not possible due to the possibility of collusion between the firms and the outside agency, information transmission is still possible through technology licensing. However, unlike the case of a cost-free honest outside agency, where information transmission always occurs under a quantity setting oligopoly, information transmission through licensing does not always occur.
Keywords: 330; asymmetric information; information transmission; licensing